Genomic and Drug Resistance Profile of Bovine Multidrug-Resistant Escherichia coli Isolated in Kazakhstan - Pavel G. Alexyuk; Andrey P. Bogoyavlenskiy; Yergali S. Moldakhanov; Kuralay S. Akanova; Adolat N. Manakbayeva; Timur Kerimov; Vladimir E. Berezin; Madina S. Alexyuk (Pathogens)
While studying the prevalence and profile of antibiotic resistance among E. coli isolated from the feces of calves with signs of colibacillosis, a strain with a wide spectrum of drug resistance was isolated. Whole-genome sequencing, followed by bioinformatic processing and the annotation of genes of this strain, showed that the genome has a total length of 4,803,482 bp and contains 4986 genes, including 122 RNA genes. A total of 31% of the genes are functionally significant and represent 26 functional groups. Additionally, 55 antibiotic resistance genes were revealed. A phenotypic drug-resistance study was performed according to CASFM and CLSI guidelines, which showed that the investigated strain was resistant to eight antibacterial drugs of different classes, including colistin. This is the first report on the AMR profile of an E. coli isolate obtained from a sick calf with evidence of escherichiosis in Kazakhstan. The provided information on the genome will be valuable in studying the evolution and development of antibiotic-resistant forms of E. coli and increase our knowledge of pathogenicity. It may also be a source for future comparative studies of the virulence and drug resistance of E. coli isolates.